Research trends and hotspots on septic shock: a bibliometric study and visualization analysis - Wang, Sitong; Li, Nan; Ma, Ben; Zhu, Shuang; Zhou, Yu; Ma, Ruihang (Frontiers in Medicine, 2024)
Background Septic shock, the most severe stage of sepsis, causes potential circulatory failure and abnormal cell metabolism which are severe enough to affect prognosis, increase mortality, and impose significant burdens on the medical system. Despite studies exploring the pathophysiology, epidemiology, and risk factors, research trends and hotspots in septic shock remain lacking. This study aims to create a visual knowledge map, identify hotspots, and predict prospective trends based on bibliometrics. We searched for publications in the WoSCC up to June 15, 2023. CiteSpace5.5 R2, VOS viewer and Pathfinder were used to evaluate the annual publications, countries, institutions, journals and keywords. We also analyzed the collaboration among countries, institutions and authors, and identified research hotspots and frontiers.Results A total of 4,208 English papers were included, and the annual publication displayed a slow upward trend. In terms of publication volume, the top three countries were the United States, France, and Germany, and the University of Pittsburgh ranked first (n=85) among all institutions, with Jeanlouis Vincent from Erasmus Medical Center (Netherlands) as the most published author (n=32). According to the collaborative network, the United States had the highest level of cooperation, and the University of Pittsburgh, the University of Toronto, and Columbia University were the institutions with the most foreign cooperation. Additionally, the co-author network revealed that scholars such as Jeanlouis Vincent, Rinaldo Bellomo, and Djillali Annane, had the strongest collaborations. The co-citation network showed that the top 3 most cited articles were: Singer M (2016), Rhodes A (2017), Dellinger RP (2013), and the top 3 most cited journals were Crit Care Med (3664), N Engl J Med (3207), Intens Care Med (3096). In the keyword co-occurrence network, the most frequent keywords were "septic shock" (2531), "sepsis" (1667), and "mortality" (569), indicating the current research hotspots. Pathobiology, fluid therapy, and endotoxic septic shock were emerging trends in research.Conclusion By using bibliometrics, this study reviewed the studies in septic shock and revealed the hotspots and cutting-edge trends, including the pathogenesis of complications, the development of biomarkers, the alternative treatments, and the rehabilitation trajectory, etc., which provided references for subsequent studies in septic shock.